Development of Warfarin Safety Monitoring Network in Phra Nakhon Si Ayutthaya Province - Choompon, Chanpen; Sunghlor, Sunisa; Khonglormyati, Jurairat (Journal of Health Science of Thailand, 2017)
Warfarin is an anticoagulant with narrow therapeutic index. Close monitoring of the degree of anticoagulation is required by blood testing (International Normalized Ratio or INR). This characteristic limits patient access to the drug at community hospital. The concept of development warfarin network is related to drug safety pharmacovigilance programme. Thus, pharmacy group of Phra Nakhon Si Ayutthaya Province and health care team are setting warfarin network in 14 community hospitals. The evaluation research included 3 steps: preparing, processing and evaluation. Aim to first, development and evaluation warfarin safety monitoring network, second analysis of drug related problems (DRPs) were carried out on 2 groups of out-patients receiving pharmacy-managed anticoagulation service at Phra Nakhon Si Ayutthaya Hospital and Sena Hospital (between 2009 & 2012) third, reporting adverse events (AEs) in 1 year (during June 2011- May 2012). Using descriptive statistics to analyzed. The results showed that warfarin alerting network development, 11 community hospitals could detect 154 patients from total 281 patients (54.8 %) in hospital databases (76 in Sena and 205 in Phra Nakhon Si Ayutthaya Hospital) via medical records and/or computer program. Second, 3 important DRPs: Non-compliance, major Adverse Events (AEs) and drug interaction were decreased in 2 big hospitals. Finally, reporting of major AEs showed 2 important events: 1 patient who receiving warfarin from University Hospital admited to Community Hospital caused by UGIB and 1 patient who receiving warfarin from Provincal Hospital was found hemorrhoid during admission to General Hospital. Conclusion, a development of drug safety monitoring network were increased quality of warfarin therapy. This study was suggested to expand warfarin network covering primary health care and used self - INR testing with strips in community hospitals.